An InIII-based anionic metal–organic framework: sensitization of lanthanide (III) ions and selective absorption and separation of cationic dyes. Issue 27 (15th June 2015) - Liu, Lin; Zhang, Xiao-Nan; Han, Zheng-Bo; Gao, Ming-Liang; Cao, Xiao-Man; Wang, Shi-Ming
Abstract : An In III -based anionic MOF exhibits sensitization of lanthanide (III) ions as well as absorption and separation of cationic dyes via ion-exchange. Abstract : An In III -based anionic framework (In III -MOF) with 4-connected SrAl2 topology was constructed. The In III -MOF with permanent porosity functions as a host for encapsulation of Ln 3+ ions through ion-exchange processes. The photophysical properties of the as-prepared Ln 3+ @In III -MOF were investigated and the results showed that the In III -MOF could serve as an antenna to sensitize Ln 3+ cations, especially suitable for Tb 3+ and Eu 3+ ions. The possible sensitization mechanism has been studied by surface photovoltage spectroscopy. Additionally, the In III -MOF could also act as a host material when applied in the separation and purification of cationic dyes, which is highly based on the size and charge of organic dyes. Moreover, it can be used as a chromatographic column stationary phase to separate cationic dyes more efficiently and selectively. It is believed that the as-prepared In III -MOF may have potential applications in optical materials and environmental fields.